013 Testosterone Positively Regulates Vagina NO-Induced Relaxation: An Experimental Study in Rats. (1st May 2022) - Comeglio, P.; Cipriani, S.; Cellai, I.; Filippi, S.; Maseroli, E.; Stasi, V. Di; Todisco, T.; Fambrini, M.; Rastrelli, G.; Maggi, M.; Vignozzi, L.
ABSTRACT: Introduction: Female sexual response is a result of a complex interplay between central and peripheral mechanisms and the nitric oxide (NO)-mediated relaxation of clitoris and distal vagina vascular bed leads to clitoris tumescence and vagina lubrification. Objective: The aim of this study was to evaluate sex steroids regulation of the relaxant/contractile pathway in vagina, using a validated animal model of ovariectomized (OVX) Sprague-Dawley rats. Methods: Subgroups of OVX rats were treated with 17β-estradiol (10 mg/kg/die), testosterone (T, 30 mg/kg/week), or testosterone and letrozole (2.5 mg/kg/die) for 6 weeks. The experimental groups were compared with a group of intact rats. In vitro contractility studies were carried out in order to investigate the effect of OVX and in vivo treatments on vaginal smooth muscle activity. RNA from vaginal tissue was analyzed by semi-quantitative RT-PCR. Results: In vitro contractility studies were performed on noradrenaline pre-contracted distal vaginal strips, isolated from each experimental group. Acetylcholine (Ach; 0.001-10 µM) stimulation induced a concentration-dependent relaxation, which was significantly reduced by NO-synthase inhibitor L-NAME (100 µM) and by guanylate cyclase inhibitor ODQ (1 µM). OVX resulted in a decreased responsiveness to Ach, restored by T supplementation, with or without letrozole, but not by 17β-estradiol. Vaginal strips sensitivity to the NO-donor SNP (1 nM - 100 µM) was higher in OVX than in the control. Vardenafil (100 nM), a PDE5 inhibitor, enhanced SNP effect in OVX+T as well as in control, suggesting that T positively modulates PDE5, as supported by RNA expression analysis. Conclusions: In vitro contractility studies and mRNA expression analysis highlight the positive regulation of T on Ach- and NO-dependent muscle relaxation by modulating the NO/cGMP/PKG pathways.Our data demonstrate that testosterone improves the NO-mediated vascular smooth muscle vaginal cells relaxation confirming its critical role in maintaining the integrity of muscular relaxant machinery. Our study confirms the decisive role played by androgens, rather than estrogens, in maintaining the functionality and integrity of the vagina. This study might provide support for the use of androgens in the treatment of genitourinary syndrome of menopause (GSM) and/or sexual arousal disorders related to ageing related-hormonal deficiency. Disclosure: Work supported by industry: no.